Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1021/acs.accounts.0c00813
|View full text |Cite
|
Sign up to set email alerts
|

Fuzziness and Frustration in the Energy Landscape of Protein Folding, Function, and Assembly

Abstract: Conspectus Are all protein interactions fully optimized? Do suboptimal interactions compromise specificity? What is the functional impact of frustration? Why does evolution not optimize some contacts? Proteins and their complexes are best described as ensembles of states populating an energy landscape. These ensembles vary in breadth from narrow ensembles clustered around a single average X-ray structure to broader ensembles encompassing a few different functional “taxonomic” states on to near co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
98
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(104 citation statements)
references
References 73 publications
(137 reference statements)
1
98
0
Order By: Relevance
“…Especially in situations in which proteins or protein complexes are required to respond to changing cellular conditions by scanning large ensembles of different RNA-molecules (Järvelin et al, 2016). As such, our finding represents a logical extension of the fuzzy protein theory for disordered proteins (Fuxreiter, 2020) by merging the fuzziness and frustration concepts in the energy landscape of proteins with that of RNA-molecules (Gianni et al, 2021). As much as frustration in fuzzy protein/protein complexes causes a multiplicity of specific interactions (Freiberger et al, 2021; Ferreiro et al, 2014) it is conceivable that frustration in RNA/protein complexes is responsible for the observed non-binary pre-mRNA-binding characteristics of the T. brucei editosome.…”
Section: Discussionmentioning
confidence: 81%
“…Especially in situations in which proteins or protein complexes are required to respond to changing cellular conditions by scanning large ensembles of different RNA-molecules (Järvelin et al, 2016). As such, our finding represents a logical extension of the fuzzy protein theory for disordered proteins (Fuxreiter, 2020) by merging the fuzziness and frustration concepts in the energy landscape of proteins with that of RNA-molecules (Gianni et al, 2021). As much as frustration in fuzzy protein/protein complexes causes a multiplicity of specific interactions (Freiberger et al, 2021; Ferreiro et al, 2014) it is conceivable that frustration in RNA/protein complexes is responsible for the observed non-binary pre-mRNA-binding characteristics of the T. brucei editosome.…”
Section: Discussionmentioning
confidence: 81%
“…Although, for two of them (A380G and L381A), the ΔΔ G was very low (<0.6 kcal/mol), thus precluding a reliable interpretation, the high Φ values of A439G (located in the C-terminal helix αC and establishing contacts with F372 in the ZA loop) observed for both the intermediate and TS2 suggest that this residue is involved in non-native interactions in both of these meta-stable states. Non-native interactions, as probed by unusual Φ values, have been found in other proteins, and it has been observed that they are often present in regions stabilizing folding intermediates [ 19 ] or in regions that are crucial for the function of the protein, such as the protein surfaces involved in recognition and binding [ 18 , 20 ]. In this context, it is interesting to note that the conformational plasticity of the ZA loop of BRDs, evidenced by molecular dynamics simulations, has been recently proposed to provide the necessary malleable interaction surface of the BRD domains to interact with their different target peptides [ 21 ].…”
Section: Resultsmentioning
confidence: 99%
“…Going into details of the NMR model, we note that while overall structure is robust to errors in the predicted sequence as shown by the comparison of the NMR models of free NCBD D/P ML and NCBD D/P AltAll , there are differences in for example helix orientations. Globular domains with a sequence identity as high as these NCBD variants (77-88%) would typically have identical structures due to a highly funneled energy landscape ( 40, 41 ), while proteins with larger structural heterogeneity have less funneled landscapes ( 1 ). Indeed, the differences between the structures of NCBD Human , NCBD D/P ML and NCBD D/P AltAll , in particular regarding the angles of the helices in relation to each other, are consistent with a less funneled energy landscape resulting in conformational heterogeneity ( 11 ).…”
Section: Discussionmentioning
confidence: 99%
“…Evolution has shaped proteins into a wide spectrum of structure, stability and dynamics, with fully disordered proteins at one end of the scale and well-folded globular proteins at the other one ( 1 ). It is becoming clear that dynamic properties per se are important for protein function ( 13 ) but it is not trivial to prove that the dynamics are essential for biological function and not merely a general property of proteins. The Nuclear Coactivator Binding Domain (NCBD) is a small (approximately 50 residues) domain from CREB-binding protein (CBP, also called CREBBP), which is a transcriptional coactivator with histone acetylase activity and present in all animals ( 4 ).…”
Section: Introductionmentioning
confidence: 99%